Supporting collaborative action for sustainable solutions: Locally-led adaptation as a policy instrument for climate change adaptation practices - Habermann, Birgit; Crane, Todd A. (International Livestock Research Institute, 2024)
The urgency of developing climate change adaptation practices that work for smallholder farmers and herders has never been greater. The United Nations Framework Convention on Climate Change and other key climate change organizations highlight the importance of research and development for locally-led adaptation (LLA) and transdisciplinary collaboration. Such an approach to adaptation promises to find climate solutions that are effective in smallholder producers’ complex environmental and socioeconomic realities and support producers as agents of change. The urgency for innovative extension and scaling pathways is compounded by the widespread degradation in African public agricultural extension services. However, despite the urgency and the widespread interest, there are few established methodologies designed to support policymakers to engage with LLA through transdisciplinary collaboration in a robust, coherent and consistent way that considers climate justice and inclusiveness. This calls for innovative tool